A Chemical Recipe for Generation of Clinical-Grade Striatal Neurons from hESCs - Wu, Menghua (Stem Cell Reports, 2018)
Differentiation of human pluripotent stem cells (hPSCs) into striatal medium spiny neurons (MSNs) promises a cell-based therapy for Huntington's disease. However, clinical-grade MSNs remain unavailable. Here, we developed a chemical recipe named XLSBA to generate clinical-grade MSNs from embryonic stem cells (ESCs). We introduced the γ-secretase inhibitor DAPT into the recipe to accelerate neural differentiation, and replaced protein components with small molecules. Using this optimized protocol we could efficiently direct regular human ESCs (hESCs) as well as clinical-grade hESCs to lateral ganglionic eminence (LGE)-like progenitors and striatal MSNs within less than half of the time than previous protocols (within 14 days and 21 days, respectively). These striatal cells expressed appropriate MSN markers and electrophysiologically acted like authentic MSNs. Upon transplantation into brains of neonatal mice or mouse model of Huntington's disease, they exhibited sufficient safety and reasonable efficacy. Therefore, this quick and highly efficient derivation of MSNs offers unprecedented access to clinical application.